Switch On/Switch Off Signal in an MOF‐Guest Crystalline Device. Issue 25 (5th July 2013) - Mazzeo, Paolo P.; Maini, Lucia; Braga, Dario; Valenti, Giovanni; Paolucci, Francesco; Marcaccio, Massimo; Barbieri, Andrea; Ventura, Barbara
Abstract: A metal organic framework (MOF) based on the [Cu4 I4 DABCO2 ] cluster (DABCO = 1, 4‐diazabicyclo[2.2.2]octane), MOF1, shows bright emission with a maximum at 556 nm and an emission quantum yield of 0.53 in the solid state. When the large cavities of the MOF are loaded during the synthesis with different amounts of ferrocene FeCp2, [(η 5 ‐C5 H5 )2 Fe II ], the luminescence of MOF1 decreases with the increase in the ferrocene content, reaching an almost complete quenching for 3.5 wt.‐% of cage loading, corresponding to the complete filling of the MOF cavities. When an electric potential is applied to the FeCp2 @MOF1 deposited onto an ITO glass, the Fe II Cp2 is oxidised to Fe III Cp2 +, and the MOF1 emission is partially switched on again, indicating that a photoinduced electron‐transfer reaction is contributing to the quenching process. Abstract : MOF1 is made of nodes based on luminescent Cu4 I4 cubane clusters and saturated amines as bridging ligands, and it is loaded with FeCp2 [(η 5 ‐C5 H5 )2 Fe II ] molecules, which quench the luminescence. When FeCp2 is oxidised to Fe III Cp2 + the emission is partially switched on again.